Bird flu hype: the spread of a disease outbreak through the media and Internet discussion groups - Hellsten, Iina; Nerlich, Brigitte (John Benjamins, 2010)
Bird flu, otherwise known as avian influenza, has attracted widespread public and global attention. The H5N1 avian influenza virus was first documented as infecting humans in Hong Kong in 1997, and many of those infected died subsequently from the virus that had been transmitted from poultry to humans. It took several years, however, before a hyped up type of public debate about bird flu began in around 2004. This article examines the hype surrounding public debates about bird flu in medical journals, newspapers and public discussion forums from 1997 to 2006. The article focuses on the development of the frequencies of published texts, and the terminology used in the three databases. The quantitative results will be accompanied by hermeneutic interpretation of the main sub-topics within the debates. These (preliminary) results contribute to research dealing with the emergence of hypes, and spread of public debates more generally.